Effect of glass powder sealings on the corrosion resistance of arc sprayed Al coating. (15th May 2019) - Wang, Runqiu; Zhou, Jianxin
Abstract: Three kinds of glass powders were employed to seal arc sprayed Al coating on P355NL1 steel in this paper. The corrosion resistances of Al coatings after sealings were investigated by immersion tests and the electrochemical measurements in 3.5% NaCl solution (with a pH value of 6.5). The morphologies, phase compositions and chemical structure of the sealed glass layers were evaluated by scanning electron microscopy (SEM), x-ray diffraction (XRD), Fourier transform infrared spectrum (FTIR). The results show that the open pores on the surface of arc sprayed Al coatings are entirely covered by the sealing layers with a thickness of about 10 microns, and the glass powders can permeate the open pores on the surface of Al coating. After immersion tests in 3.5 wt% NaCl solutions (a pH value of 6.5), the sealed Al coating with three kinds of glass powders have better corrosion resistance than arc sprayed Al coating. But the top surface of the sealing layers with three glass powders become relatively loose, especially for the sealing layers with 400 °C and 500 °C glass powders. According to the analyses of XRD and FTIR, K+, Na+, and Ca 2+ in the sealing layers can be captured by H + in NaCl solution. Compared with the arc sprayed Al coating, three glass sealing layers have more positive corrosion potential and lower corrosion current density in anode according to the electrochemical corrosion results, and the corrosion resistance of Al coating can be enhanced significantly by the sealing layers. By comparison, the sealing with 680 °C glass powder has better corrosion resistance and structure stability.